Isolation of potential zoonotic Mycobacterium spp. from diseased freshwater angelfish (Pterophyllum scalare) from an aquarium - Cardoso, P. H. M.; Moreno, L. Z.; Ikuta, C. Y.; Rodrigues, M. V. [UNESP]; Donola, S. T.; Heinemann, M. B.; Balian, S. C.; Moreno, A. M. (Instituto Internacional de Ecologia, 2022)
Nontuberculous mycobacteria infection is one of the most common chronic bacterial diseases in ornamental aquarium fish and appears to be directly related to stressful husbandry practices. Furthermore, it also represents zoonotic potential. Here we present the isolation and characterization of non-tuberculous mycobacteria from diseased freshwater angelfish (Pterophyllum scalare) in São Paulo, Brazil. Nine discarded breeding females with signs of disease were evaluated. The fish exhibited lethargy, loss of appetite, cachexia, skin ulcers, and exophthalmia. At necropsy, four fishes presented macroscopic granulomas in the spleen. Mycobacterium chelonae, M. fortuitum, M. gordonae, M. intracellulare and M. peregrinum were isolated and identified by hsp65 PCR restriction analysis. Histopathological analysis revealed microscopic lesions compatible with mycobacteriosis, and Mycobacterium bacillus were observed by Ziehl-Neelsen stain. Notably, all Mycobacterium species identified in this study have already been reported in human patients; therefore, diseased animals may be a source of infection for people who handle fish and aquariums.

A infecção por micobactérias não tuberculosas é uma das doenças bacterianas crônicas mais comuns em peixes ornamentais de aquário e parece estar diretamente relacionada a práticas de manejo estressantes. Além disso, também representa potencial zoonótico. Aqui, apresentamos o isolamento e a caracterização de micobactérias não tuberculosas de peixes-anjo de água doce doentes (Pterophyllum scalare) em São Paulo, Brasil. Foram avaliadas nove fêmeas reprodutoras descartadas com sinais de doença. Os peixes exibiam letargia, perda de apetite, caquexia, úlceras cutâneas e exoftalmia. Na necropsia, quatro peixes apresentaram granulomas macroscópicos no baço. Mycobacterium chelonae, M. fortuitum, M. gordonae, M. intracellulare e M. peregrinum foram isolados e identificados por análise de restrição por PCR de hsp65. A análise histopatológica revelou lesões microscópicas compatíveis com micobacteriose, e o bacilo de Mycobacterium foi observado pela coloração de Ziehl-Neelsen. Notavelmente, todas as espécies de Mycobacterium identificadas neste estudo já foram relatadas em pacientes humanos; portanto, animais doentes podem ser uma fonte de infecção para pessoas que manipulam peixes e aquários.
Isolamento de Mycobacterium spp. potencialmente zoonótica de peixes anjo de água doce (Pterophyllum scalare) doentes de um aquário
Keywords: Mycobacterium; freshwater angelfish; granuloma; PCR; Mycobacterium; peixe-anjo de água doce; granuloma; PCR